2019
DOI: 10.1093/annonc/mdz005
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-selection of metastatic colorectal cancer patients using next-generation sequencing to improve clinical efficacy of anti-EGFR therapy

Abstract: Conclusions: No improvement in the selection of patients for anti-EGFR therapy was obtained by adjusting the mutation detection threshold in tissue samples from 5% to 1% MAF. Response to anti-EGFR was significantly better in patients with quadruple wild-type tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
(22 reference statements)
3
18
0
1
Order By: Relevance
“…32 A recent large multicenter retrospective analysis that compared standard-of-care RAS testing with NGS multigene assessment reported no improvement in the selection of patients for anti-EGFR therapy by lowering the threshold in tissue samples from 5% to 1% MAF. 33 As expected, in this study anti-EGFR treatment was significantly better in mCRC patients with KRAS/NRAS/BRAF/PIK3CA WT tumors. 33 Of note, in the CAPRI-GOIM study we found in 7/10 cases of low KRAS mutational load the presence of additional mutations in PIK3CA, TP53, BRAF, ERBB2, FGFR3, and/or FBXW7 genes, which could equally contribute to anti-EGFR cancer cell resistance.…”
Section: Tumor Heterogeneity For Ras Braf and Pi3kca Mutations And supporting
confidence: 82%
See 1 more Smart Citation
“…32 A recent large multicenter retrospective analysis that compared standard-of-care RAS testing with NGS multigene assessment reported no improvement in the selection of patients for anti-EGFR therapy by lowering the threshold in tissue samples from 5% to 1% MAF. 33 As expected, in this study anti-EGFR treatment was significantly better in mCRC patients with KRAS/NRAS/BRAF/PIK3CA WT tumors. 33 Of note, in the CAPRI-GOIM study we found in 7/10 cases of low KRAS mutational load the presence of additional mutations in PIK3CA, TP53, BRAF, ERBB2, FGFR3, and/or FBXW7 genes, which could equally contribute to anti-EGFR cancer cell resistance.…”
Section: Tumor Heterogeneity For Ras Braf and Pi3kca Mutations And supporting
confidence: 82%
“…33 As expected, in this study anti-EGFR treatment was significantly better in mCRC patients with KRAS/NRAS/BRAF/PIK3CA WT tumors. 33 Of note, in the CAPRI-GOIM study we found in 7/10 cases of low KRAS mutational load the presence of additional mutations in PIK3CA, TP53, BRAF, ERBB2, FGFR3, and/or FBXW7 genes, which could equally contribute to anti-EGFR cancer cell resistance. These findings highlight the existence of a subgroup of mCRC with a mixed genotype, which is characterized by different potentially driver mutations that affect the EGFR pathway.…”
Section: Tumor Heterogeneity For Ras Braf and Pi3kca Mutations And supporting
confidence: 82%
“…In particular, digital PCR shows the highest sensitivity, up to a limit of detection of 0.001% for digital droplet PCR [8,9,10] and about 0.1–1% for conventional quantitative PCR [11,12,13]. However, recent reports show how the highest sensitivity of the technique does not reflect a better prediction of the response to anti-EGFR agents, as it may include rare KRAS mutant subclones that do not have clinical significance [14,15,16]. The concordance between tissue and liquid biopsies in mCRC, on the other hand, is strictly related not only to the technology used for tissue and plasma analyses, but also to some clinical parameters of the patients, such as the presence or absence of liver metastases [13,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A major point of discussion is whether the optimal threshold of the RAS mutant allele fraction to identify patients likely to benefit from anti-EGFR drugs should be 1% or 5%. We used a threshold of 5% as it has been reported that reducing the threshold to 1% does not improve outcomes [ 36 , 37 ]. We found one sensitive patient (P28) who harbored the A146V KRAS mutation at 5%.…”
Section: Discussionmentioning
confidence: 99%